Evaluation of Malaria Diagnostic Methods as a Key for Successful Control and Elimination Programs - Afoma Mbanefo; Nirbhay Kumar (Tropical Medicine and Infectious Disease, 2020)
Malaria is one of the leading causes of death worldwide. According to the World Health Organization’s (WHO’s) world malaria report for 2018, there were 228 million cases and 405,000 deaths worldwide. This paper reviews and highlights the importance of accurate, sensitive and affordable diagnostic methods in the fight against malaria. The PubMed online database was used to search for publications that examined the different diagnostic tests for malaria. Currently used diagnostic methods include microscopy, rapid diagnostic tests (RDT), and polymerase chain reaction (PCR). Upcoming methods were identified as loop-mediated isothermal amplification (LAMP), nucleic acid sequence-based amplification (NASBA), isothermal thermophilic helicase-dependent amplification (tHDA), saliva-based test for nucleic-acid amplification, saliva-based test for Plasmodium protein detection, urine malaria test (UMT), and transdermal hemozoin detection. RDT, despite its increasing false negative, is still the most feasible diagnostic test because it is easy to use, fast, and does not need expensive equipment. Noninvasive tests that do not require a blood sample, but use saliva or urine, are some of the recent tests under development that have the potential to aid malaria control and elimination. Emerging resistance to anti-malaria drugs and to insecticides used against vectors continues to thwart progress in controlling malaria. Therefore, future innovation will be required to enable the application of more sensitive and affordable methods in resource-limited settings.